Evaluasi Kinerja Pengadaan Suku Cadang Kapal pada Perusahaan Pelayaran - Zaroni, Zaroni; Yuana, Desy; Abidin, Zaenal; Saribanon, Euis (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2025)
In 2022, PT XYZ, a shipping company in Indonesia, experienced 42 cases of ship lease termination due to machinery damage, which was related to delays in procuring ship spare parts, however no procurement performance measurement had been conducted in the company. The purpose of this research is to evaluate the procurement performance at PT XYZ and what kind of improvement could be made by the company. The research was conducted using SCOR model with a Fishbone diagram to identify the root causes of the emerging constraints and determine the corrective actions that could be taken. From the research results, it is found that the procurement performance of PT XYZ has not yet met the target, where the gap in RL2.1 On Time Fulfilment is 71.65% from the company’s target, the average gap in RS2.2 Fulfil Cycle is 45.08 days from seven days, and the gap in RS2.3 Deliver Cycle Time is an average of 30.8 days from the target of 14 days. The contributing factors are primarily due to the operational areas of the ships being spread across Indonesia, a limited vendor population, the scarcity of machine parts manufactured in certain countries, and the machinery longevity. PT XYZ could implement optimizing the population of partner suppliers in each ship operational zone, collaborating with foreign suppliers, and optimizing spare parts stock both on the ship and in the warehouse as the performance improvement strategies.